2010
DOI: 10.1001/archgenpsychiatry.2010.127
|View full text |Cite
|
Sign up to set email alerts
|

Very Early Predictors of Adolescent Depression and Suicide Attempts in Children With Attention-Deficit/Hyperactivity Disorder

Abstract: Context Major depression and dysthymia in adolescence are associated with substantial disability, need for mental health services, and risk for recurrence. Concrete suicidal ideation and attempts during adolescence are particularly associated with significant distress, morbidity, and risk for completed suicide. Objectives To test the hypothesis that young children with attention-deficit/hyperactivity disorder (ADHD) are at increased risk for depression and suicidal ideation and attempts during adolescence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
258
2
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 321 publications
(304 citation statements)
references
References 38 publications
29
258
2
8
Order By: Relevance
“…With higher base‐rate levels of emotional problems among girls in the general Swedish population 74, the associations between ADHD and internalizing/emotional problems reported here could to some extent be explained by covariation. However, higher rates of internalizing and/or emotional problems among girls with ADHD have been commonly reported in both clinical and population‐ or community‐based studies 8, 16, 19, 29, 46, 75, 76, 77, 78, 79, 80, 81. Thus, ADHD symptoms seem to contribute to the total internalizing problem load in a gender‐specific manner 61.…”
Section: Discussionmentioning
confidence: 99%
“…With higher base‐rate levels of emotional problems among girls in the general Swedish population 74, the associations between ADHD and internalizing/emotional problems reported here could to some extent be explained by covariation. However, higher rates of internalizing and/or emotional problems among girls with ADHD have been commonly reported in both clinical and population‐ or community‐based studies 8, 16, 19, 29, 46, 75, 76, 77, 78, 79, 80, 81. Thus, ADHD symptoms seem to contribute to the total internalizing problem load in a gender‐specific manner 61.…”
Section: Discussionmentioning
confidence: 99%
“…Because a number of large prevalence studies have suggested that the male: female ratio of the disorder may be markedly lower than once believed, especially in adulthood (e.g., DuPaul et al, 2001;Kessler et al, 2005;Ramtekkar et al, 2010;Simon et al, 2009), research on ADHD in young women presents an urgent area of need (see also Gaub & Carlson, 1997;Gershon, 2002). Overall, girls with ADHD may be at particularly high risk for negative outcomes over time (see Babinski et al, 2011;Biederman et al, 2010Biederman et al, , 2012Chronis-Tuscano et al, 2010;Dalsgaard, Mortensen, Frydenberg, & Thomsen, 2002;Hinshaw et al, 2012).…”
Section: Adhd In Femalesmentioning
confidence: 99%
“…In addition, individuals with MDD and ADHD experience higher levels of substance use and psychosocial impairment than disorder in isolation [32][33][34][35], suggesting a potential variant of MDD, and therefore explaining the treatment resistance in this population when treated with traditional SSRIs.…”
Section: Attention Deficit Hyperactivity Disorder (Adhd)mentioning
confidence: 99%